(untitled) (XXI Century. Spanish Literature and Culture, 2015)
The first novels of Rafael Chirbes, En la lucha final (1991) y La buena letra (1992) have so far deserved little attention from critics. However, in those early texts, Chirbes offers a critical view of the Transition from the intra-histories of two completely different universes, one around the world of culture, another in a humble Valencian people. Its protagonists act as bulwarks to show that falsehood, imposture, forgetfulness, folds and lies became keys and ways of being in social change.